Octanoyl-carnitine predicts post operative complications following coronary artery bypass surgery - Pierre-Alain Bahr (Scientific Reports, 2025)
Abstract We aimed to evaluate the prognostic value of octanoyl-carnitine in patients undergoing surgical myocardial revascularization for coronary artery disease. We conducted a retrospective analysis of an existing prospective cohort aimed at studying risk factors for vasoplegia in patients undergoing cardiac surgery with cardiopulmonary bypass. We conducted our study exclusively on patients included in the prospective cohort at Dijon University Hospital in 2021. We included 42 adult patients undergoing coronary artery bypass grafting, either alone or combined with another surgical procedure. We collected plasma samples for each patient from EDTA-anticoagulated tubes, taken as part of routine biological check-ups according to the department protocol, at three time points: preoperatively, immediately postoperatively in the intensive care unit, and on the first postoperative day. Liquid chromatography coupled with tandem mass spectrometry was used to determine plasma levels of acyl-carnitines, including octanoyl-carnitine. The primary endpoint was the occurrence of major postoperative complications (stroke, atrial fibrillation, acute kidney injury, and/or death). Fourteen patients (33%) had major postoperative complications. Octanoyl-carnitine plasma concentration significantly increased during the perioperative period and was significantly associated with major postoperative complications at all three time points in coronary artery bypass grafting patients (T1: 14.2 [11.6; 18.6] vs 21.1 [14.8; 28.0], T2: 20.9 [16.4;27.9] vs 34.8 [21.2;37.2], T3: 22.8 [13.7;30.9] vs 34.4 [30.2;41.2]; p < 0.05; in nmol/l). At baseline, octanoyl-carnitine levels were higher in patients with complications, while other acyl-carnitines showed no significant differences. Octanoyl-carnitine is associated with mitochondrial metabolism and could be evaluated alone or in conjunction with clinical scores.